The impact of crystallization conditions on structure‐based drug design: A case study on the methylene blue/acetylcholinesterase complex - Dym, Orly (Protein Sci, 2016)
Structure‐based drug design utilizes apoprotein or complex structures retrieved from the PDB. >57% of crystallographic PDB entries were obtained with polyethylene glycols (PEGs) as precipitant and/or as cryoprotectant, but <6% of these report presence of individual ethyleneglycol oligomers. We report a case in which ethyleneglycol oligomers' presence in a crystal structure markedly affected the bound ligand's position. Specifically, we compared the positions of methylene blue and decamethonium in acetylcholinesterase complexes obtained using isomorphous crystals precipitated with PEG200 or ammonium sulfate. The ligands' positions within the active‐site gorge in complexes obtained using PEG200 are influenced by presence of ethyleneglycol oligomers in both cases bound to W84 at the gorge's bottom, preventing interaction of the ligand's proximal quaternary group with its indole. Consequently, both ligands are ∼3.0Å further up the gorge than in complexes obtained using crystals precipitated with ammonium sulfate, in which the quaternary groups make direct π‐cation interactions with the indole. These findings have implications for structure‐based drug design, since data for ligand‐protein complexes with polyethylene glycol as precipitant may not reflect the ligand's position in its absence, and could result in selecting incorrect drug discovery leads. Docking methylene blue into the structure obtained with PEG200, but omitting the ethyleneglycols, yields results agreeing poorly with the crystal structure; excellent agreement is obtained if they are included. Many proteins display features in which precipitants might lodge. It will be important to investigate presence of precipitants in published crystal structures, and whether it has resulted in misinterpreting electron density maps, adversely affecting drug design.